Dangerous deception - Kehret, Peg (Dutton Children's Books, an imprint of Penguin Group (USA) LLC, 2014)
Sixth-grader Emmy and her classmates start a secret community service project to help a hungry family, but soon Emmy finds herself involved in a home burglary ring operated by the family's neighbor.